Magnitude and Trends of Chronic Liver Disease: A Retrospective Hospital Based Study in Eastern Amhara Region, Northeast Ethiopia - Minwuyelet Maru Temesgen; Seid Legesse Hassen; Birtukan Shiferaw Ayalew; Anteneh Demelash Abate; Nega Berhe Belay (Journal of Spleen And Liver Research, 2023)
A retrospective study quantifies chronic liver disease burden and trends in Eastern Amhara. It summarizes demographics, etiologies, and outcomes to inform regional planning.
Keywords: liver